Legacies of power in American music : essays in honor of Michael J. Budds - Budds, Michael J., 1947-2020; Mabary, Judith (Abingdon, Oxon ; New York, NY : Routledge, 2023)
This volume honors and extends the contributions of educator and scholar Dr. Michael J. Budds to the field of musicology, particularly the study of American music. As the longtime editor of two book series for the College Music Society, Budds nurtured a wide range of scholarship in American music and had a lasting impact on the field. This book brings together scholars who worked with Budds as a colleague, editor, or mentor to carry on his legacy of passionate engagement with America's rich and varied musical heritage. Ranging through jazz, gospel, Americana, and film music to American classical, and addressing music's social contexts and analytical structure, the research gathered here attests to the diversity of the mosaic that is American music and the numerous scholarly approaches that have been taken to the subject.
Keywords: Music -- United States; MUSIC / General; MUSIC / History & Criticism